English medium instruction in higher education in Asia-Pacific from policy to pedagogy - Fenton-Smith, Ben; Humphreys, Pamela; Walkinshaw, Ian (Cham, Switzerland Springer International Publishing AG, 2017)
This volume draws together the viewprints and research findings of leading scholars and informed local practitioner-researchers throughout Asia-Pacific about the issues and challenges of English as a medium of instruction (EMI) at higher education institutions in that region.
Keywords: English language -- Study and teaching (Higher) -- Pacific Area; English language -- Pacific Area; Education, higher -- Pacific Area; Language and education -- Pacific Area